Adipokine profile in long-term juvenile dermatomyositis, and associations with adipose tissue distribution and cardiac function: a cross-sectional study. Issue 1 (24th February 2023) - Marstein, Henriette Schermacher; Witczak, Birgit Nomeland; Godang, Kristin; Olarescu, Nicoleta Christina; Schwartz, Thomas; Flatø, Berit; Molberg, Øyvind; Bollerslev, Jens; Sjaastad, Ivar; Sanner, Helga
Abstract : Objectives: In long-term juvenile dermatomyositis (JDM), altered adipose tissue distribution and subclinical cardiac dysfunction have been described. Our aims were to compare adipokine levels in patients with JDM after long-term disease with controls, and explore associations between adipokines and (1) adipose tissue distribution and (2) cardiac function. Methods: The study cohort included 59 patients with JDM (60% female, mean age 25.2 years, mean disease duration 16.9 years), and 59 age/sex-matched controls. Updated Pediatric Rheumatology International Trials Organization criteria for clinically inactive JDM were used to stratify patients into active (JDM-active) or inactive (JDM-inactive) disease groups. Lipodystrophy was clinically assessed in all patients. In all study participants, we measured adipose tissue distribution by dual-energy X-ray absorptiometry and cardiac function by echocardiography. Serum adipokines (adiponectin, apelin-12, lipocalin-2, leptin, visfatin and resistin) were analysed using ELISA. Results: Patients with JDM had higher leptin levels compared with controls (p≤0.01). In JDM-active, apelin-12 and visfatin were higher compared with JDM-inactive (p≤0.05). In JDM-total and JDM-active, lower adiponectin correlated with lipodystrophy and total fat mass. Also, systolic dysfunction correlated with: lower adiponectin in JDM-total, JDM-inactive and JDM-active, and with lower apelin-12 in JDM-total and JDM-active and resistin in JDM-active (all p≤0.05). Lower adiponectin correlated with diastolic dysfunction in JDM-total and JDM-active. Conclusion: After long-term disease, leptin levels were unfavourably regulated in patients with JDM compared with controls, and apelin-12 and visfatin in JDM-active versus JDM-inactive. We found associations between adipokines and both adipose tissue distribution and cardiac systolic function in all patients with JDM, which was most prominent in patients with active disease.